Partial endoscopic papillosphincterotomy with balloon dilatation in the treatment of choledocholithiasis - V. B. Rinchinov; A. N. Plekhanov (Вестник хирургии имени И.И. Грекова)
This paper contained data from different literature about problem of minimally invasive treatment of patients with choledocholithiasis. The clinical example justified the use of partial papillosphincterotomy with balloon dilatation in the case of large choledocholithiasis. It was shown that the use of this operation did not increase the risk of intra and postoperative complications during the lithoextraction of large stones from the biliary tract.